Design optimization of MEMS dual-leg shaped piezoresistive microcantilever - Ab Rahim, Rosminazuin; Bais, Badariah; Yeop Majlis, Burhanuddin; Sheik, Fareed (2013)
In this paper, an optimization on the mechanical behaviour of silicon piezoresistive microcantilever (PRM) has been carried out. Using CoventorWare 2008, the mechanical behavior of the PRM structure was investigated by studying few contributing factors that affect the performance of the device. The performance was represented with mechanical displacement of the suspended PRM sensor with regards to various factors such as the microcantilever shape and geometrical dimensions, the materials and the effect of incorporating stress concentration region (SCR) on the device structure. In this research work, a single-layer piezoresistive microcantilever in which both piezoresistor and microcantilever structures are made of the same material of single-crystalline silicon is utilized. Two dual-leg shaped piezoresistive microcantilever designs have been proposed:piezoresistive microcantilever with and without a square hole. From the simulation results, it can be seen that the maximum displacement is observed at maximum microcantilever’s length and minimum thickness. The incorporation of a square hole as an SCR not only shows a significant increase in Mises stress value but also in the displacement of the microcantilever structure. Single-crystalline Si was chosen as the device material for the fabrication of single-layer piezoresistive microcantilever due to its high piezoresistive coefficients and thermal conductivity.